(untitled) (Pedagogy of Higher and Secondary Education, 2009)
In the field of education innovative activity is investigated by pedagogical innovatiks. A concept "innovation" in it is the major gnosiological reference point. The article is devoted to the problem of existence of different opinions as for the determination of the essence of such concepts as « innovations, enovations, «innovative activity»